AÃ§Ã£o de fitoreguladores no potencial osmÃ³tico foliar do tomateiro (ð˜“ð˜ºð˜¤ð˜°ð˜±ð˜¦ð˜³ð˜´ð˜ªð˜¤ð˜¶ð˜® ð˜¦ð˜´ð˜¤ð˜¶ð˜ð˜¦ð˜¯ð˜µð˜¶ð˜® Mill. cv. "Roma") - Castro, Paulo R. C.; Pacheco, Carlos R. V. M. (REVISTA DE AGRICULTURA, 2020)
AÃ§Ã£o de fitoreguladores no potencial osmÃ³tico foliar do tomateiro (ð˜“ð˜ºð˜¤ð˜°ð˜±ð˜¦ð˜³ð˜´ð˜ªð˜¤ð˜¶ð˜® ð˜¦ð˜´ð˜¤ð˜¶ð˜ð˜¦ð˜¯ð˜µð˜¶ð˜® Mill. cv. "Roma")